PENGARUH KOMPENSASI KOMISARIS DAN DIREKSI TERHADAP LABA PERUSAHAAN, DENGAN CORPORATE GOVERNANCE SEBAGAI PEMODERASI - Mochamad - Muslih (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2018)
The purpose of this research is to study the impact of commissioners’ compensation and directors’ compensation on firm profit, with corporate governance as moderating variable. This research used quantitative method. Secondary data were used for this research. As many as 47 companies listed in Indonesia Stock Exchange and classified as LQ-45 were sampled for this research. The result showed that commissioner compensation and director compensation has no significant impact on firm profit and CG moderation to commissioners and directors compensation were also not significant. The effect of firm size to firm profit was also not significant. Key words: commisioners compensation , directors compensation, profit, corporate governance.